(untitled) (Jurnal Sosial Ekonomi Pertanian, 2023)
Cayenne pepper is a potential commodity to be cultivated because of its high selling value. In addition, the business opportunity for cayenne pepper is also high along with the high demand for cayenne pepper in Indonesia and abroad. This study aims to analyze the factors that influence the purchasing decision of cayenne pepper simultaneously and partially. The research method used is descriptive quantitative. Sampling was carried out by accidental sampling with a sample of 100 respondents. This study uses primary data obtained from interviews, questionnaires, and observations as well as secondary data obtained from books, journals, articles, and the Internet. Variable measurement uses a Likert scale which is then transformed with the Successive Interval Method (MSI). Test the data instrument using a validity test and reliability test. The classic assumption test used the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing using multiple linear regression analysis. The result of this study is that cultural, social, personal, and psychological factors influence purchasing decisions simultaneously. Partially social factors (X2), personal factors (X3), and psychological factors (X4) significantly influence the purchasing decision of cayenne pepper with a positive coefficient. Cultural factors (X1) have no significant effect on the decision to buy cayenne pepper.